Habitat preferences dictate amphibian assemblage and diversity in Langkawi Island, Kedah, Peninsular Malaysia - Nur Johana Johari,; Norhayati Ahmad,; Amirrudin Ahmad,; Ehwan Ngadi,; Muzzneena Ahmad Mustapha,; Grismer, Larry Lee (Penerbit Universiti Kebangsaan Malaysia, 2021)
Various habitats found on Langkawi Island such as agricultural fields, peat swamps, lowland forests, upland forests, and riverine forests are occupied by many species of anuran fauna. These variations provide a platform to explore species diversity, distribution, and other ecological parameters to understand the distribution patterns and to facilitate the management of important species within particular areas. The objective of this study was to compare species richness of anuran species in different types of habitat on Langkawi Island, Malaysia. We surveyed seven types of habitat, namely agriculture (AG), coastal (CL), forest (FT), pond (PD), fisherman village near estuarine mangrove (FVM), riparian forest (RF), and river (RV). A total of 775 individuals were recorded, representing 23 species from 14 genera and six families known to occur on Langkawi Island. Forest (FT) and riparian forest (RF) (both forest habitats) indicated relatively high values of Shannon Index (H’), 2.60 and 2.38 respectively, compared to the other non-forest habitats, CL (1.82), RV (1.71), FVM (1.56), PD (1.54), and AG (1.53). Rank abundance curves showed that the majority of disturbed habitats displayed geometric series models and broken stick models, whereas forest habitat types (FT and RF) represented log normal models. The performance of species richness estimators varied but Chao 1 estimator performed well for many sampled habitat types and showed the tendency to coalesce with Sobs (Mao Tau) curves except for CL and FVM. As expected, the forested habitat (FT and RF) was more diverse in species diversity compared to those of non-forest groups. Nevertheless, non-forested species were found in abundance, highlighting the relevance of these habitats in supporting the amphibian fauna. This study highlights the importance of habitat types in structuring species diversity and community structures and suggest that the information may be useful to improve conservation practices of inland amphibian habitats.